KEANEKARAGAMAN JENIS ANGGREK DI JALUR PENDAKIAN WIRAYANA GUNUNG CAKRABUANA KABUPATEN MAJALENGKA - Hermawan, Riki; Hendrayana, Yayan; Adhya, Ilham (Universitas Nusa Bangsa, 2023)
The existence of orchids in nature continues to decline due to habitat destruction and overexploitation. Conservation efforts that have been carried out so far have often experienced difficulties due to insufficient data and information as a basis for management, including conservation areas. The more widespread forest destruction will result in these species being threatened with extinction. This study aims to determine the diversity of orchid species, on the Wirayana Mount Cakrabuana Climbing Path. The information is expected to provide an initial contribution to the area management and orchid conservation efforts on the Wirayana Mount Cakrabuana Climbing Path. This research was conducted by means of a vegetation survey, sampling and documentation by exploring the existence of orchids. The sampling technique used the path transect method. The number of transects used is one line transect with a line length of 1500 m with a total of 22 sample plots. Data analysis was carried out by calculating the Important Value Index (INP), Species Dominance Index (Di) and Species Diversity Index (H'). The results showed that in the natural forest area of ​​Mount Cakrabuana there were 22 species of individuals which included 7 species of terrestrial orchids and 15 species of epiphytic orchids with a total of 243 individuals found. From the results of the calculation of species diversity, it is stated that the diversity of orchid species in the natural forest area of ​​Mount Cakrabuana is classified as moderate (2,973). This information is very important, especially for area managers in preserving the biodiversity of Mount Cakrabuana, especially orchids in the future.